2
$\begingroup$

I am interested in the improper integral: $$I=\int_{-\infty}^\infty 1-e^{-\frac{1}{x^2}}{\rm d}x=2\int_{0}^\infty 1-e^{-\frac{1}{x^2}}{\rm d}x$$ which I am fairly sure converges.

I broke the integral into one over $1$ and one over the exponential and then tried to evaluate this through a change to polar coordinates similar to the way to evaluate the Gaussian Integral.

However, when I attempt to introduce the variable change $\frac{1}{x}=u$ to apply the polar coordinates, I am left with the bounds being $\lim_{\epsilon\to0}[\epsilon,-\epsilon]$. I am not sure of how to convert these bounds into polar form in terms of $r$ and $\theta$. If anyone can give me a hint of where to continue, what I am doing wrong, or if there is a better way of evaluating this integral it would be greatly appreciated.

$\endgroup$
  • 1
    $\begingroup$ @Simply Beautiful Art Are you sure? $1-e^{-0}=0$. $\endgroup$ – Professor Vector Dec 14 '17 at 15:34
  • $\begingroup$ @ProfessorVector Oops, my bad. $\endgroup$ – Simply Beautiful Art Dec 14 '17 at 15:35
  • $\begingroup$ $I=2\sqrt{\pi}$, I think, but I'll have to write that up later. $\endgroup$ – Professor Vector Dec 14 '17 at 15:37
  • $\begingroup$ @ProfessorVector That makes sense, I expect the answer to be of the form $\sqrt{\pi}$ due to the similarity to the Gaussian Integral. $\endgroup$ – aleden Dec 14 '17 at 15:39
4
$\begingroup$

As I said I would, I'll add my two cents (it's more or less self-explanatory, I hope): \begin{align}\int^\infty_0(1-e^{-1/x^2})\,dx&=\int^\infty_0\frac{1-e^{-x^2}}{x^2}\,dx \\&=\int^\infty_0\int^1_0e^{-ax^2}\,da\,dx \\&=\int^1_0\int^\infty_0e^{-ax^2}\,dx\,da \\&=\int^1_0\frac{\sqrt{\pi}}{2\sqrt{a}}\,da \\&=\sqrt{\pi} \end{align}

$\endgroup$
4
$\begingroup$

Notice that

$$\int e^{-\frac{1}{x^{2}}}{\rm d}x=\int 1\cdot e^{-\frac{1}{x^{2}}}{\rm d}x=$$

$$=xe^{-\frac{1}{x^{2}}}-\int \frac{2}{x^{2}}e^{-\frac{1}{x^{2}}}{\rm d}x$$

using integration by parts. For the last integral, define $u=\frac{1}{x}$ and ${\rm d}u=-\frac{1}{x^{2}}{\rm d}x$ to get

$$-\int \frac{2}{x^{2}}e^{-\frac{1}{x^{2}}}{\rm d}x=2\int e^{-u^{2}}{\rm d}u=\sqrt{\pi}{\rm erf}\left(u\right)=\sqrt{\pi}{\rm erf}\left(\frac{1}{x}\right)$$

Can you take it from here?

$\endgroup$
  • $\begingroup$ Thank you, I will get back to you after I evaluate. $\endgroup$ – aleden Dec 14 '17 at 15:57
1
$\begingroup$

With Laplace transform properties, let $\dfrac{1}{x^2}=u$ so you have \begin{align} J &= \int_{0}^\infty 1-e^{-\frac{1}{x^2}}{\rm d}x \\ &= \dfrac12\int_0^\infty\dfrac{1-e^{-u}}{u\sqrt{u}}du \\ &= \dfrac12\int_0^\infty\dfrac{\Gamma\left(\dfrac12\right)}{s^\frac12}-\dfrac{\Gamma\left(\dfrac12\right)}{(s+1)^\frac12}ds \\ &= \dfrac12\Gamma\left(\dfrac12\right)\left(2\sqrt{s}-2\sqrt{s+1}\right)_{0}^\infty \\ &= \color{blue}{\sqrt{\pi}} \end{align}

$\endgroup$
  • $\begingroup$ I think the area should be positive, right? $\endgroup$ – aleden Dec 14 '17 at 15:58
  • $\begingroup$ You should consider explaining the equality between Lines 2 and 3. $\endgroup$ – Mark Viola Dec 14 '17 at 16:00
  • $\begingroup$ @MyGlasses You should have $$\Big[2\sqrt{s}-2\sqrt{s+1}\Big]_{0}^{\infty}=0-(-2)=2$$ It explain your wrong minus sign. $\endgroup$ – eranreches Dec 14 '17 at 16:01
  • $\begingroup$ @eranreches Thanks. I see your comment now! $\endgroup$ – Nosrati Dec 14 '17 at 16:06

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.